1999
DOI: 10.1038/sj.cdd.4400483
|View full text |Cite
|
Sign up to set email alerts
|

Small stress protein Hsp27 accumulation during dopamine-mediated differentiation of rat olfactory neurons counteracts apoptosis

Abstract: The small stress protein Hsp27 is expressed during mammalian neural development. We have analyzed the role of this protein in immortalized rat olfactory neuroblasts. In the presence of dopamine a fraction of these cells differentiate into neurons while the remaining cells undergo apoptosis. We report here that the dopamine induced differentiation and apoptosis are associated with a transient and specific accumulation of Hsp27. Moreover, transfection experiments have shown that Hsp27 overexpression drastically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 40 publications
0
58
0
3
Order By: Relevance
“…6 Hsp27 is highly expressed in neuronal cells and is shown to protect against neuronal cell apoptosis. 7 Mehlen et al 8 reported an increase in Hsp27 expression and Hsp27-dependent protection against apoptosis during dopamine-induced, cAMP-dependent differentiation of rat olfactory neuroblasts. Since there are direct parallels between survival and differentiation in these two experimental systems, we hypothesised that Hsp27 may represent a downstream target of the Brn3a transcription factor during neuronal cell survival and differentiation.…”
Section: Dear Editormentioning
confidence: 99%
“…6 Hsp27 is highly expressed in neuronal cells and is shown to protect against neuronal cell apoptosis. 7 Mehlen et al 8 reported an increase in Hsp27 expression and Hsp27-dependent protection against apoptosis during dopamine-induced, cAMP-dependent differentiation of rat olfactory neuroblasts. Since there are direct parallels between survival and differentiation in these two experimental systems, we hypothesised that Hsp27 may represent a downstream target of the Brn3a transcription factor during neuronal cell survival and differentiation.…”
Section: Dear Editormentioning
confidence: 99%
“…The group of Arrigo has proposed that HSP25 could play a role as a switch between cell differentiation and apoptosis. 27,28 In ES cells or olfactory neurons undergoing differentiation, a transient expression of HSP25 accompanies arrest of cell proliferation and entry into differentiation. When this increase is altered, more cells undergo apoptosis.…”
Section: Hsp25 and Chondrocyte Differentiationmentioning
confidence: 99%
“…24 ± 26 Another role has been proposed by the laboratory of Dr. A-P Arrigo : it could act as a switch between differentiation and apoptosis as demonstrated during cell line differentiation in vitro. 27,28 This role has been correlated with reduced glutathione regeneration in response to stress. 29,30 But the cellular mechanism is not clearly identified yet for the action of HSP25 in the differential control of differentiation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock protein 27 (HSP27), a human form of small heat shock protein (in murine system, HSP25 is present and these two forms have homology of more than 90%), has been suggested to protect cells from apoptotic cell death triggered by hyperthermia, ionizing radiation, oxidative stress, Fas ligand, and cytotoxic drugs (10)(11)(12). Several mechanisms have been proposed to account for the HSP27-mediated apoptotic protection.…”
Section: Introductionmentioning
confidence: 99%